DESAIN PROTOTIPE KAPAL PENANGKAP DI PERAIRAN MALUKU - Alberth Ch Nanlohy; Mulyono S. Baskoro; Budhi H. Iskandar; Domu Simbolon (Jurnal Teknologi Perikanan dan Kelautan, 2011)
Design prototype teknology which will be developed has better excellence if compared to condition of the existing fishing vessel. Its the excellences can have an effect on to operation of ship and sumberdaya fishery in water territory of Maluku sea. Expansion of design joran fishing by using fiber glass has lighter excess, strong, and durable although the price expensive but can be made balance to with haul obtained by means of catch. Side that also usage of styro foam hardly having an effect on to ship design huhate proposed to be developed and has some excellences of if compared to ship used by the existing fisherman. At ship with inboard engine, fish hold design only yield product for local marketing and has not been modified to yield product skipjack loin which is a form of export product, this latter the product request would very height.